Arabidopsis ECHIDNA protein is involved in seed coloration, protein trafficking to vacuoles, and vacuolar biogenesis. (23rd March 2020) - Ichino, Takuji; Maeda, Kazuki; Hara-Nishimura, Ikuko; Shimada, Tomoo
Abstract: Flavonoids are a major group of plant-specific metabolites that determine flower and seed coloration. In plant cells, flavonoids are synthesized at the cytosolic surface of the endoplasmic reticulum and are sequestered in the vacuole. It is possible that membrane trafficking, including vesicle trafficking and organelle dynamics, contributes to flavonoid transport and accumulation. However, the underlying mechanism has yet to be fully elucidated. Here we show that the Arabidopsis ECHIDNA protein plays a role in flavonoid accumulation in the vacuole and protein trafficking to the vacuole. We found defective pigmentation patterns in echidna seed, possibly caused by reduced levels of proanthocyanidins, which determine seed coloration. The echidna mutant has defects in protein sorting to the protein storage vacuole as well as vacuole morphology. These findings indicate that ECHIDNA is involved in the vacuolar trafficking pathway as well as the previously described secretory pathway. In addition, we found a genetic interaction between echidna and green fluorescent seed 9 ( gfs9 ), a membrane trafficking factor involved in flavonoid accumulation. Our findings suggest that vacuolar trafficking and/or vacuolar development, both of which are collectively regulated by ECHIDNA and GFS9, are required for flavonoid accumulation, resulting in seed coat pigmentation. Abstract : An Arabidopsis thaliana mutant lacking the trans -Golgi network-localized protein ECHIDNA shows vacuole-related phenotypes, including altered seed coloration, vacuolar protein sorting, and vacuolar morphology.